Advanced Photocatalysts for Energy Conversion and Environmental Applications - Liang, Ruowen (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Photocatalysis is an advanced technique that transforms solar energy into sustainable fuels and oxidizes pollutants via the aid of semiconductor photocatalysts. The main scientific and technological challenges toward effective photocatalysis are the stability, robustness, and efficiency of semiconductor photocatalysts. For major practical applications in energy conversion (i.e., hydrogen evolution, CO2 reduction, and oriented synthesis) and environmental remediation (i.e., air purification and antibacterial and wastewater treatment), highly efficient and stable photocatalysts need to be developed. This Special Issue collects published original researches on synthesizing novel photocatalytic materials and their application in energy conversion and environmental remediation.